Undernutrition of dairy cattle in smallholder production systems in East Africa - Osuji, P.O.; Saarisalo, E.M.; Tegegne, Azage; Umunna, N.N. (International Livestock Research Institute, 2005)
Variations in availability and nutritional quality of feed resources in the tropics affect cattle production under smallholder production systems. This results in undernutrition of cattle because of fluctuations in feed and nutrient supply. The term undernutrition is very complex and not clearly understood. The end products from animal production in the forms of body growth, milk yield, reproduction and traction power are expressed as a result of the influence of undernutrition. The mechanisms involved in physiological changes need to be understood. In this paper, attempt is made to define undernutrition in cattle, how and when it occurs and its causes and manifestations. The focus is on improving milk and meat production and on increasing the efficiency of use of traction animals. Studies undertaken by the International Livestock Research Institute (ILRI) on improving milk production under smallholder production systems have focused on feed resources development, feeding systems, improving feed use and on management strategies for different classes of dairy animals. Strategies to improve milk production in the tropics, managing oxen to improve work performance and the effects of level of feeding on carcass composition are explained based on studies undertaken in East Africa. ILRI's work on undernutrition in ruminants in crop-livestock systems of the sub-humid zone of West Africa and for the semi-arid (Sahel) zone are also presented.